Preliminary studies on in situ monitoring of lactose crystallization using focused beam reflectance measurement - Karthik Pandalaneni; Jayendra K. Amamcharla (Kansas Agricultural Experiment Station Research Reports, 2014)
Isothermal crystallization of lactose was studied at supersaturated concentrations (w/w) of 50%, 55%, and 60% at temperatures 20ºC and 30ºC using an in situ system, focused beam reflectance measurement (FBRM), and a refractometer. The FBRM data were compared with Brix readings taken over time using a refractometer during isothermal crystallization. Chord length distribution obtained from FBRM in the ranges of<50>Î¼m (fine crystals) and 50 to 300 Î¼m (coarse crystals) were observed and evaluated in relation to the extent of crystallization and rate constant results deduced from the refractometer measurements. The measured fine crystal counts increased with supersaturated concentration and temperature during isothermal crystallization. On the other hand, coarse counts were observed to increase with decreasing supersaturated concentration and temperature. The total crystal counts (coarse + fine crystals) obtained from FBRM increased as the temperature increased at all concentrations. The robustness of FBRM in understanding isothermal lactose crystallization at various concentrations and temperatures was successfully evaluated in the study.; Dairy Day, 2014, Kansas State University, Manhattan, KS, 2014; Dairy Research, 2014 is known as Dairy Day, 2014
Keywords: Dairy Day; 2014; Kansas Agricultural Experiment Station contribution; no. 15-156-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1111; Lactose crystallization; Focused beam reflectance measurement